Regional ion channel gene expression heterogeneity and ventricular fibrillation dynamics in human hearts - Sivagangabalan Gopal (PLOS ONE, 2014)
RATIONALE: Structural differences between ventricular regions may not be the sole determinant of local ventricular fibrillation (VF) dynamics and molecular remodeling may play a role. OBJECTIVES: To define regional ion channel expression in myopathic hearts compared to normal hearts, and correlate expression to regional VF dynamics. METHODS AND RESULTS: High throughput real-time RT-PCR was used to quantify the expression patterns of 84 ion-channel, calcium cycling, connexin and related gene transcripts from sites in the LV, septum, and RV in 8 patients undergoing transplantation. An additional eight non-diseased donor human hearts served as controls. To relate local ion channel expression change to VF dynamics localized VF mapping was performed on the explanted myopathic hearts right adjacent to sampled regions. Compared to non-diseased ventricles, significant differences (p<0.05) were identified in the expression of 23 genes in the myopathic LV and 32 genes in the myopathic RV. Within the myopathic hearts significant regional (LV vs septum vs RV) expression differences were observed for 13 subunits: Nav1.1, Cx43, Ca3.1, Cavalpha2delta2, Cavbeta2, HCN2, Na/K ATPase-1, CASQ1, CASQ2, RYR2, Kir2.3, Kir3.4, SUR2 (p<0.05). In a subset of genes we demonstrated differences in protein expression between control and myopathic hearts, which were concordant with the mRNA expression profiles for these genes. Variability in the expression of Cx43, hERG, Na(+)/K(+) ATPase ss1 and Kir2.1 correlated to variability in local VF dynamics (p<0.001). To better understand the contribution of multiple ion channel changes on VF frequency, simulations of a human myocyte model were conducted. These simulations demonstrated the complex nature by which VF dynamics are regulated when multi-channel changes are occurring simultaneously, compared to known linear relationships. CONCLUSIONS: Ion channel expression profile in myopathic human hearts is significantly altered compared to normal hearts. Multi-channel ion changes influence VF dynamic in a complex manner not predicted by known single channel linear relationships.